ответ:-2 7/15
Пошаговое объяснение:
7
10
−3
1
6
=
−
3 · 6 + 1
19
3 · 7
3 · 10
5 · 19
5 · 6
21
30
95
21 − 95
=−
74
37 · 2
15 · 2
37
15
=−2
≈ −2.4666666666667
1) 7,10-3 1/6=3 14/15
Надеюсь я правельно понял.Если не правельно,то простить.
ответ:-2 7/15
Пошаговое объяснение:
7
10
−3
1
6
=
7
10
−
3 · 6 + 1
6
=
7
10
−
19
6
=
3 · 7
3 · 10
−
5 · 19
5 · 6
=
21
30
−
95
30
=
21 − 95
30
=−
74
30
=−
37 · 2
15 · 2
=−
37
15
=−2
7
15
≈ −2.4666666666667
1) 7,10-3 1/6=3 14/15
Пошаговое объяснение:
Надеюсь я правельно понял.Если не правельно,то простить.